2022
DOI: 10.3389/fendo.2022.816229
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Exposed to Persistently High Glucocorticoid Levels Develop Insulin-Resistance and Altered Lipolysis: A Promising In Vitro Model to Study Cushing’s Syndrome

Abstract: BackgroundIn Cushing’s syndrome (CS), chronic glucocorticoid excess (GC) and disrupted circadian rhythm lead to insulin resistance (IR), diabetes mellitus, dyslipidaemia and cardiovascular comorbidities. As undifferentiated, self-renewing progenitors of adipocytes, mesenchymal stem cells (MSCs) may display the detrimental effects of excess GC, thus revealing a promising model to study the molecular mechanisms underlying the metabolic complications of CS.MethodsMSCs isolated from the abdominal skin of healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…MSCs are multipotent cells residing in multiple tissues with the capacity for selfrenewal and differentiation into various cell types [9,10]. Our previous works confirmed that different pathologies, ranging from the dermatologic to the fibrotic ones [11][12][13][14][15][16][17][18][19][20], arise at the staminal level: MSCs show the same dysregulated pathological properties found in differentiated cells, opening up the hypothesis that the onset of the diseases could be backdated at the stem level.…”
Section: Introductionmentioning
confidence: 54%
“…MSCs are multipotent cells residing in multiple tissues with the capacity for selfrenewal and differentiation into various cell types [9,10]. Our previous works confirmed that different pathologies, ranging from the dermatologic to the fibrotic ones [11][12][13][14][15][16][17][18][19][20], arise at the staminal level: MSCs show the same dysregulated pathological properties found in differentiated cells, opening up the hypothesis that the onset of the diseases could be backdated at the stem level.…”
Section: Introductionmentioning
confidence: 54%
“…After stained for 1 h, they were washed three times with PBS and then photographed at 200× magnification. Intracellular Oil Red O was dissolved using 100% isopropyl alcohol for 5 min, and the content of lipid droplets was quantified spectrophotometrically by measuring the absorbance at 510 nm [38,39].…”
Section: Oil Red O Stainingmentioning
confidence: 99%
“…Scuteri et al [ 463 ], however, observed that incubating rat MSCs with rat islets was sufficient to differentiate the MSCs into PDX1-expressing and insulin-secreting cells, suggesting that factors secreted by islets (e.g., insulin) can affect the phenotype of the interacting MSCs. Although the direct effect of insulin as a single differentiation factor on MSCs has not yet been documented, insulin has been shown to increase glucose uptake and GLUT4 translocation in MSCs [ 464 ]. The ability of MSCs to adhere to the islets [ 463 ] and to home to the islets following transplantation, where it improves β-cell function, suggests a mutual interaction between the two cell types.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%